POLA KOMUNIKASI INTERPERSONAL GURU PAI TERHADAP KEBERHASILAN BELAJAR SISWA PADA MI ASSALAM MARTAPURA DAN SD MUHAMMADIYAH MARTAPURA KABUPATEN BANJAR - Latifah Latifah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2019)
In this study, researchers used quantitative approach method because the data used in general in the form of numbers calculated through statistical tests. while the specification is descriptive correlational analytics. Namely this research describes the systematic, factual, and meticulous also trying to give an idea of what has to do with later research, analyze to find solutions to problems encountered. In the results of observations conducted on two schools in the District of Banjar, namely Madarasah Ibtidaiyah Assalam Martapura and SD Muhammadiyah Martapura, where the two schools are private status, in both schools are often encountered that factors that affect this learning include teaching methods, curriculum relation of educator with student, student relation with student, discipline, lesson, falisility and time, learning standard, building condition, learning method and home duty. Learning to teach is a core behavior in the educational process in which students and educators interact. The interaction of teaching and learning is supported by several other factors in education, among others: educational objectives, educators, students, nature and educational facilities, teaching methods, subject matter and environment.Keywords: Interpersonal Communication, Successful Learning